2016
DOI: 10.1038/srep33432
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human mitochondrial ferritin promoter: identification of transcription factors and evidences of epigenetic control

Abstract: Mitochondrial ferritin (FtMt) is an iron storage protein belonging to the ferritin family but, unlike the cytosolic ferritin, it has an iron-unrelated restricted tissue expression. FtMt appears to be preferentially expressed in cell types characterized by high metabolic activity and oxygen consumption, suggesting a role in protecting mitochondria from iron-dependent oxidative damage. The human gene (FTMT) is intronless and its promoter region has not been described yet. To analyze the regulatory mechanisms con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Two‐sample t ‐test was used for statistical analysis. ** P < 0.01. GA representation of the reported transcription factors for the mitochondrial ferritin promoter (Guaraldo et al , 2016). The locations of putative binding sites for transcription are boxed: Positive transcription factors (SP1, CREB, and YY1) are in red, while negative transcription factors (GATA2, FoxA1, and C/EBPβ) are in blue. Source data are available online for this figure.…”
Section: Resultsmentioning
confidence: 99%
“…Two‐sample t ‐test was used for statistical analysis. ** P < 0.01. GA representation of the reported transcription factors for the mitochondrial ferritin promoter (Guaraldo et al , 2016). The locations of putative binding sites for transcription are boxed: Positive transcription factors (SP1, CREB, and YY1) are in red, while negative transcription factors (GATA2, FoxA1, and C/EBPβ) are in blue. Source data are available online for this figure.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Roflumilast could phosphorylate CREB to up-regulate the level of FtMt, and the promoter region of FtMt was reported to harbor the binding site of CREB [ 17 ], which implicated that the increased expression of FtMt in ovarian cancer was attributed to the transcription of CREB. To confirm the binding site of CREB within FtMt promoter region in ovarian cancer, the luciferase reporter assays were performed by using Calyculin A which was demonstrated to be the activator of CREB.…”
Section: Resultsmentioning
confidence: 99%
“…SIRT3 loss increases ROS production, bringing about elevated IRP1 binding to IREs and increased TfR-1 expression as a consequence [70]. Mitochondrial ferritin (FTMT) appears regulated by a complex mechanism involving epigenetic events, such as histone de-acetylases recruitment and GC islands accumulation at its promoter, and interplay between transcription factors, such as CREB, SP1, and YY1 [71]. Nuclear factor erythroid 2-like 2 (NRF2) and myeloid zinc finger-1 (MZF-1) could impact cancer cell growth by transcriptionally regulating FPN, FTH, and FTL expression in prostate and breast cancer [72].…”
Section: Iron and Epigenetic Regulation In Cancermentioning
confidence: 99%